Domestic Violence and Privacy - Stepanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
The notion of privacy is crucial to the issue of domestic violence. While traditional libertarian definition of privacy which stems from Locke’s private/public divide does not allow state intervention into private and family matters, and therefore justifies domestic violence, radical feminism eliminates the divide altogether and initiates creation of a number of legal instruments which are legitimising control over private life, but fails to predict that this will lead to double repression over victims who are being controlled both by perpetrators and the state which controls their private lives. The aim of this paper is to contribute to the present debates on privacy and domestic violence and help create a new definition of privacy, which would be a compromise between the two radically opposed views. According to this new definition, privacy is not opposed to control but is rather coupled with it, and this definition should help address the problem of domestic violence in a more adequate way.